PENERAPAN PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF, MENYENANGKAN, GEMBIRA DAN BERBOBOT DENGAN MODEL TEAMS GAMES AND TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SD INPRES KOLONGAN - Tudus, Melisa Veronika (Jurnal Analisis Pendidikan Sosial, 2024)
The purpose of this research is to improve student learning outcomes in Mathematics through the Application of Active, Innovative, Creative, Effective, Fun Learning with Teams Games and Tournament Models in the learning process. This research is a classroom action research using the research subjects of class V SD Inpres Kolongan as many as 20 people. This research was carried out in 2 cycles, each cycle having one meeting. In the first cycle there are 4 stages that will be carried out, namely planning, carrying out observations and reflections. And in the second cycle, it is focused on the implementation stage to maximize the achievement of indicators. Data collection techniques used include research and test instruments. Based on the results of the study, in the first cycle the results were 74% and in the second cycle the learning outcomes were 94%. Thus, from the first and second cycles there was an increase of 20%. Thus, it can be concluded that the application of Active, Innovative, Creative, Effective, Fun Learning with the Teams Games and Tournament Model in the learning process can improve the learning outcomes of fifth graders of SD Inpres Kolongan towards FPB and KPK learning.